Neoadjuvant Crizotinib in Advanced Inflammatory Myofibroblastic Tumour with ALK Gene Rearrangement. Issue 2 (March 2015) - Rafee, Shereen; Elamin, Yasir Y.; Joyce, Eimear; Toner, Mary; Flavin, Richard; McDermott, Ronan; Sheehy, Niall; Hennessy, Bryan; O'Byrne, Kenneth; Gleeson, Noreen; Osman, Nemer
Background: Inflammatory myofibroblastic tumours (IMTs) are rare sarcomas that were first described in the lung. They are composed of myofibroblastic mesenchymal spindle cells accompanied by an inflammatory infiltrate of plasma cells. Complete resection is the treatment of choice. There is currently no standard treatment for inoperable or recurrent disease. Expression of ALK protein triggered by ALK gene rearrangement at chromosome 2p23 has been found in 36%-60% of IMTs. Case report: We report a rapid early response to crizotinib as neoadjuvant therapy, enabling surgical excision of a large ALK (-translocated IMT, which resulted in complete disease clearance. To the best of our knowledge, this is the first case in the literature of a patient with IMT in whom crizotinib was used successfully in the neoadjuvant or curative setting.